The collaborative economy in Poland and Europe: A tool for boosting female employment? - Karolina Beaumont (Center for Social and Economic Research (CASE), 2016)
The collaborative economy is a relatively new economic approach based on peer-to-peer transactions. It includes the shared creation, production and consumption of goods and services accessible for all through online platforms and smartphone applications. It is a burgeoning business model that is experiencing increased interest in all European countries. Statistics show that Poland already has an above-average number of women who are interested in self-employment. Furthermore, formal female employment in Poland is quite low by European standards. This situation implies great potential for the development of the participation of women in the collaborative economy. The paper "The Collaborative Economy in Poland and Europe: A Tool for Boosting Female Employment?" by Karolina Beaumont discusses the challenges of the collaborative economy as a system stimulating female social and economic empowerment and assesses the opportunities offered by the collaborative economy in increasing the female labour participation rate amongst Polish women.
Keywords: J16; J21; J23; J24; 330; collaborative economy; sharing economy; new business models; gender equality; self-employment; female employment